2014
DOI: 10.1016/j.apsb.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of high level aminoglycoside resistance in Acinetobacter baumannii from Beijing, China

Abstract: The objective of this study was to investigate the genetic basis of high level aminoglycoside resistance in Acinetobacter baumannii clinical isolates from Beijing, China. 173 A. baumannii clinical isolates from hospitals in Beijing from 2006 to 2009 were first subjected to high level aminoglycoside resistance (HLAR, MIC to gentamicin and amikacin>512 µg/mL) phenotype selection by broth microdilution method. The strains were then subjected to genetic basis analysis by PCR detection of the aminoglycoside modifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 18 publications
5
27
2
Order By: Relevance
“…The prevalence of armA genes in A. baumannii isolates has been described in several studies that showed 50% (52/104) in strains isolated in Lishui, eastern China (10), 60.4% (61/101) in clinical strains in Vietnam (53), and 59.54% (103/173) in hospitals in Beijing, China (54). In the present study, 45.76% (54/118, Table IV) of isolates harbored the armA gene, which is similar to the above cases reported in China.…”
Section: Discussionmentioning
confidence: 92%
“…The prevalence of armA genes in A. baumannii isolates has been described in several studies that showed 50% (52/104) in strains isolated in Lishui, eastern China (10), 60.4% (61/101) in clinical strains in Vietnam (53), and 59.54% (103/173) in hospitals in Beijing, China (54). In the present study, 45.76% (54/118, Table IV) of isolates harbored the armA gene, which is similar to the above cases reported in China.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, rmtB is a 16S rRNA methylase which confers resistance to almost all aminoglycosides except streptomycin [48]. This ability was verified in UY1PSABAL and was confirmed harbouring the rmtB gene and consequently displayed resistance to all tested aminoglycosides (amikacin, gentamicin, gentamicin and tobramycin) represented by AMK R GEN R NET R TOB R .…”
Section: Plos Onementioning
confidence: 83%
“…Nie et al proposed that increased aminoglycoside resistance in A. baumannii is related to acc (6ʹ). 29 Another study reported the presence of acetyltransferase genes (aacC1) in 63.3% of Acinetobacter isolates and other genes including aphA6, aadA1 and aadB were detected in 65%, 41.7% and 3.3%, of the isolates, respectively. 30 In our study the prevalence of aphA6 and aadA1 genes was less prevalent than reported previously.…”
Section: Discussionmentioning
confidence: 98%